Refinement of Modified Endoscopic Lateral Soft-Tissue Procedure for Correction of Hallux Valgus Deformity - Tun Hing Lui, M.B.B.S. (H.K.), F.R.C.S. (Edin.), F.H.K.A.M., F.H.K.C.O.S.; Charles Churk Hang Li, M.B.C.h.B., M.R.C.S. (H.K.), F.R.C.S.Ed. (Ortho.), F.H.K.C.O.S., F.H.K.A.M. (Ortho.); Amanda Mun Yee Slocum, M.B.B.S. (H.K.), M.R.C.S. (H.K.), F.R.C.S.Ed. (Ortho.), F.H.K.C.O.S., F.H.K.A.M. (Ortho.); Siu Kei Kam, M.B.Ch.B. (Arthroscopy Techniques)
Hallux valgus is a common orthopaedic problem, and surgical correction frequently is indicated for symptomatic deformity. The modified endoscopic distal soft-tissue procedure has been reported to provide a minimally invasive approach of hallux valgus correction with augmentation of the medial metatarsosesamoid suspensory ligament and intermetatarsal ligament. The purpose of this Technical Note is to describe the refinements of the modified endoscopic distal soft-tissue procedure to achieve more anatomical augmentation of the medial metatarsosesamoid ligament and intermetatarsal ligament, which can provide more stable reconstruction and prevent stiffness of the first metatarsophalangeal joint.